PPO.05 Early fetal fibronectin testing at 18 weeks' predicts spontaneous preterm birth, though accuracy is improved with combined CL testing. (9th June 2014) - Hezelgrave, NL; Seed, P; Tribe, RM; Shennan, AH
Abstract : Introduction: Cervical length measurement and fetal fibronectin (fFN) testing are recognised predictors of spontaneous preterm birth. Fetal fibronectin testing is traditionally used from 22 weeks' gestation. Its value at earlier gestations using a quantitative test (qfFN) in combination with CL measurement is unknown. Methods: A prospective predefined analysis of a cohort of asymptomatic women at high-risk of preterm birth, who underwent qfFN testing and ultrasonographic cervical length (CL) assessment at 18–21+6 weeks (n = 479). End-point: sPTB < 34 weeks gestation. Results: 200ng/ml. 25% (45/479) of women had CL of <25 mm, 37% of whom had sPTB <34 weeks'. For those women with qfFN >200 ng/ml, the PPV for sPTB <34 weeks' was 26.5%. The PPV increased to 55.6% if the CL was <25 mm and reduced to 16.0% if the CL was ≥25 mm (Chi 2 p = <0.05). For women with qfFN <10 ng/ml, sPTB prevalence of 3.7% increased to 20% with a short cervix, and reduced to 3.1% if the cervix was 'normal' (Chi 2 p = <0.05). Conclusion: qfFN is valid for screening for sPTB at 18 weeks A combined CL scan and qfFN test would be a more sensitive predictor of outcome at 18 weeks' gestation than either alone. This earlier gestation could target prophylactic interventions more appropriately.